Estrategias comunicacionales para la difusión de la nueva temporada del canal de YouTube las Delicias de Samin año 2022 - Aguay Angulo, Daniela Estefania (2022)
The YouTube channel "Las delicias de Samín", arises as an alternative in the relationship between parents and children and the positive use of technology. Samín is a young referent of the good use of these tools through the audiovisual proposal. During the first season (April-December 2020) several problems related to the pre, pro and post-production processes were identified, among other intrapersonal behaviors of the work team due to the presence of COVID-19, personal, emotional, technical, technological, and operational. However, according to the diagnosis of the program's production situation and the results of the surveys, it is necessary to work on the second season, through a new proposal that incorporates communication strategies framed in the phases of launching, visibility, trust, positioning, and expansion, in order to ensure sustainability and permanence in all social networks.